2018
DOI: 10.1007/s12017-018-8495-9
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine Improves Lipopolysaccharide-Induced Amyloidogenesis by Suppressing NF-KappaB Pathway

Abstract: Amyloidogenesis is known to cause Alzheimer’s disease. Our previous studies have found that lipopolysaccharide (LPS) causes neuroinflammation and amyloidogenesis through activation of nuclear factor kappaB (NF-κB). Piperlongumine (PL) is an alkaloid amide found naturally in long pepper (Piper longum) isolates; it was reported to have inhibitory effects on NF-κB activity. We therefore investigated whether PL exhibits anti-inflammatory and anti-amyloidogenic effects by inhibiting NF-κB. A murine model of LPS-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Recent studies also showed that piperlongumine possess highly potent anti-neuroinflammatory functions. In vitro studies showed that piperlongumine significantly attenuated the production of proinflammatory mediators (NO and PGE 2 ) and some cytokines (TNF-α and IL-6) by suppressing NF-κB signaling pathway in LPS induced BV-2 microglias, primary astrocytes, RAW264.7 macrophages and Jurkat cells [13,397,398]. Some important insights into the anti-neuroinflammatory and neuroprotective effects of piperlongumine have come from recent studies using animal models.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also showed that piperlongumine possess highly potent anti-neuroinflammatory functions. In vitro studies showed that piperlongumine significantly attenuated the production of proinflammatory mediators (NO and PGE 2 ) and some cytokines (TNF-α and IL-6) by suppressing NF-κB signaling pathway in LPS induced BV-2 microglias, primary astrocytes, RAW264.7 macrophages and Jurkat cells [13,397,398]. Some important insights into the anti-neuroinflammatory and neuroprotective effects of piperlongumine have come from recent studies using animal models.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
“…Some important insights into the anti-neuroinflammatory and neuroprotective effects of piperlongumine have come from recent studies using animal models. Accordingly, piperlongumine inhibited LPS-induced memory impairment, Aβ accumulation and the activities of β- and γ-secretases in murine models [397]. Gu et al [398], reported that the paralytic severity and neuropathology in mice model of experimental autoimmune encephalomyelitis (EAE) induced by myelin oligodendrocyte glycoprotein 35–55 immunization were reduced in piperlongumine-treated group in comparison with the EAE model group.…”
Section: Biological Activities Piper Plantsmentioning
confidence: 99%
“…Firstly, based on the strategy of network pharmacology, the interaction network of known sciatica-related genes was constructed, and the key candidate targets of intervention of Piper longum L. on sciatica-related imbalance network were selected. It was found that the key targets of Piper longum L. were significantly enriched in several pathways related to the pathological process of sciatica, among which NF-kB signaling pathway, a member protein of this signaling pathway, especially PPARG and NF-kB1, were closely related to the inflammatory response in the pathological process of sciatica [41].…”
Section: Discussionmentioning
confidence: 99%
“…Piperlongumine can inhibit amyloidogenesis by inhibiting NF-κB activity. Evidence also suggests that piperlongumine injections inhibited LPS-induced memory [49].…”
Section: Other Therapeutic Activities Of Piper Amidesmentioning
confidence: 99%